2021
DOI: 10.1186/s13014-021-01800-x
|View full text |Cite
|
Sign up to set email alerts
|

Split-VMAT technique to control the deep inspiration breath hold time for breast cancer radiotherapy

Abstract: Background To improve split-VMAT technique by optimizing treatment delivery time for deep-inspiration breath hold (DIBH) radiotherapy in left-sided breast cancer patients, when automatic beam-interruption devices are not available. Methods Ten consecutive patients were treated with an eight partial arcs (8paVMAT) plan, standard of care in our center. A four partial arcs (4paVMAT) plan was also created and actual LINAC outputs were measured, to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…However, the DIBH technique has shown a longer beam-on time and treatment time which could lead to uncertainty of treatment delivery. Poeta et al demonstrated the 4 partial arcs split-VMAT plan could signi cantly reduce treatment delivery time from 8.9 mins to 5.4 mins compared to conventional treatment and each partial arc around 30 seconds which similar to our study (average partial arc approximately 27 seconds) [20]. Base on their feedback from treatment delivery, most patients were able to comfortably hold their breath for more than 20s, the feasibility of our technique should be further analyzed.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, the DIBH technique has shown a longer beam-on time and treatment time which could lead to uncertainty of treatment delivery. Poeta et al demonstrated the 4 partial arcs split-VMAT plan could signi cantly reduce treatment delivery time from 8.9 mins to 5.4 mins compared to conventional treatment and each partial arc around 30 seconds which similar to our study (average partial arc approximately 27 seconds) [20]. Base on their feedback from treatment delivery, most patients were able to comfortably hold their breath for more than 20s, the feasibility of our technique should be further analyzed.…”
Section: Discussionsupporting
confidence: 77%
“…Intensity-modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT) have been increasingly used to improve plan quality for PMRT and shown to achieve better conformity and homogeneity of PTV, but more scattering doses are obtained in critical organs especially for ipsilateral lung and heart [14][15][16][17][18]. While many studies have discussed the bene t of IMRT and VMAT for PMRT, the e ciency of IMRT has been reported to show more monitor units (MUs) and longer delivery time [19,20]. In this study, we have developed unique VMAT and Hybrid VMAT (H-VMAT) techniques that produce more conformal target volume coverage, excellent homogeneity in the planning target volume, and the acceptable dose of organs at risk for the PMRT patients.…”
Section: Introductionmentioning
confidence: 99%
“…For the whole process, an overall analysis from plan design and implementation to prognosis was conducted. Moreover, the deep inspiration breathhold (DIBH) technology can significantly reduce the radiation dose that the heart and lungs are exposed to during breast cancer radiotherapy (34,35). However, the treatment involving free breathing is still the conventional procedure for treating PMRT patients at our center.…”
Section: Discussionmentioning
confidence: 99%